Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Slope Stability Analysis for Landslide in Road Preservation Working Packages Ende - Wolowaru and Junction – Kelimutu Sta 10+475 Fauzan Akbar, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto Subgrade Stabilization with Ca(OH)2 Lime to Improve the Physical and Mechanical Properties of Soil (Case Study: The National Road Trengguli – Bts. Kab. Demak/Kudus) Rahmadsyah Rangkuti, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Comparison of Three Embankment Reinforcement on Soft Soil, A Case Study of Calang – Simpang Peut Road Section Doni Mardian, Indrasurya B Mochtar & Dedy Mandarsyah The Impact of Coal Combustion Waste (Fly Ash and Bottom Ash) on The Properties of Clay Soil (Case Study: National Road Section Demak – Kudus, Indonesia) Alien Maulida Nurtaqwim, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Existing Design Analysis of Slope Reinforcement on Clayey Soil and Its modified Alternatives (Case Study : Awunio – Lapuko National Road, Southeast Sulawesi) Zahrial Firman R, Mohamad Khoiri & Freddy Siagian